An Analysis of Mustafa Afridi's Sng-E-Mah as an Adaptation of Shakespeare's Hamlet - Kamran Zaib,; Irfan Ullah,; Muhammad Anwar,; Zubair Ahmad,; Shahzad Khan, (Al-Qanṭara, 2023)
This research article explores the 2022 Pakistani drama series, "Sng-e-Mah," written by Mustafa Afridi, as an adaptation of William Shakespeare's Hamlet. Through a detailed analysis of the plot, characters, and themes of both works, this article argues that "Sng-e-Mah" adapts Hamlet to a contemporary Pakistani context, while also retaining the essence of Shakespeare's original tragedy. By examining the cultural and historical context of both works, this article highlights how "Sng-e-Mah" explores universal themes of love, revenge, and betrayal, while also addressing issues specific to Pakistani society. Overall, this article argues that "Sng-e-Mah" is a successful adaptation of Hamlet that engages with both Shakespearean and Pakistani cultural traditions.